2023
DOI: 10.1177/07356331231210946
|View full text |Cite
|
Sign up to set email alerts
|

Assessing Computational Thinking, Motivation, and Grit of Undergraduate Students Using Educational Robots

Nikolaos Pellas

Abstract: Educational technologists and practitioners have made substantial strides in developing affordable digital and tangible resources to support both formal and informal computer science instruction. However, there is a lack of research on practice-based assignments, such as Internet of Things (IoT) projects, that allow undergraduate students to design and demonstrate educational robots using digital or physical assistance, especially when it comes to computational thinking (CT) and programming skills development … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 45 publications
1
1
0
Order By: Relevance
“…The results revealed that adopting technology into educational practices, in designing instructional activities, assessing student assignments, and homework can accelerate science learning, motivation, interaction in online discussions, and stimulate students' creative thinking. This observation was supported by [9][10][11]13,14]. Furthermore, the qualitative part of the study corroborated the quantitative findings, further emphasizing the usefulness of digital technology in both educational and professional settings.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…The results revealed that adopting technology into educational practices, in designing instructional activities, assessing student assignments, and homework can accelerate science learning, motivation, interaction in online discussions, and stimulate students' creative thinking. This observation was supported by [9][10][11]13,14]. Furthermore, the qualitative part of the study corroborated the quantitative findings, further emphasizing the usefulness of digital technology in both educational and professional settings.…”
Section: Discussionsupporting
confidence: 75%
“…Modern technologies and their educational applications facilitate relaying scientific knowledge to students through investigation and experimentation [9]; they increase students' effective participation in the educational process and develop their creative and critical thinking skills, self-efficacy, and self-regulation [10,11]; they enhance learning aptitude [12], motivation [13], computer skills [14], and online interactions [15,16]; they offer students access to various information sources compared to the limitedness of traditional teaching; and they equitably provide students with the continuity of learning through life. Such benefits of modern technologies in education represent an integral part of the education sustainable development goal (SDG4) [17].…”
Section: Introductionmentioning
confidence: 99%